Penggunaan Game Based Learning untuk Efektifitas Pembelajaran di SD Muhammadiyah Pakel - Ahmad Ahsin Maulana; Muhammad Izzul Muslimin; Muhammad Fajar Kurniyawan; Pandhit Eka Cahya Saputra (Penerbit Widina, Widina Media Utama, 2026)
Game-Based Learning (GBL) is an innovative learning approach that uses games as the primary tool in the teaching and learning process. This approach is designed to enhance students’ learning motivation, participation, and understanding through enjoyable and meaningful experiences. This article explains the concept of Game-Based Learning, its theoretical foundations, characteristics, benefits, and methods of implementation in learning, particularly within the Indonesian educational context. The article also discusses the advantages and limitations of this approach, as well as strategies for using it effectively in accordance with learning objectives.ABSTRAKGame Based Learning (GBL) adalah salah satu cara belajar yang inovatif dengan menggunakan permainan sebagai alat utama dalam proses belajar mengajar. Pendekatan ini dibuat agar bisa meningkatkan semangat belajar, partisipasi, dan pemahaman siswa melalui pengalaman yang menyenangkan dan bermakna. Artikel ini menjelaskan konsep Game Based Learning, dasar teori, ciri-cirinya, manfaatnya, serta cara penerapannya dalam pembelajaran, terutama di lingkungan pendidikan Indonesia. Artikel ini juga membahas kelebihan dan kekurangan dari pendekatan ini, serta cara menggunakannya secara efektif sesuai dengan tujuan pembelajaran.